2014
DOI: 10.1109/tvcg.2014.2346919
|View full text |Cite
|
Sign up to set email alerts
|

EvoRiver: Visual Analysis of Topic Coopetition on Social Media

Abstract: Cooperation and competition (jointly called "coopetition") are two modes of interactions among a set of concurrent topics on social media. How do topics cooperate or compete with each other to gain public attention? Which topics tend to cooperate or compete with one another? Who plays the key role in coopetition-related interactions? We answer these intricate questions by proposing a visual analytics system that facilitates the in-depth analysis of topic coopetition on social media. We model the complex intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(48 citation statements)
references
References 37 publications
0
47
0
Order By: Relevance
“…Twitter users use closely related words or adopt similar linguistic styles to express their interest in related issues (e.g., Economy, Employment, and Spending), which makes it easier to capture the cooperation, instead of competition, between social issues [38, 39]. The contrasting findings may also be attributed to the pairwise interaction that is examined in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twitter users use closely related words or adopt similar linguistic styles to express their interest in related issues (e.g., Economy, Employment, and Spending), which makes it easier to capture the cooperation, instead of competition, between social issues [38, 39]. The contrasting findings may also be attributed to the pairwise interaction that is examined in this study.…”
Section: Discussionmentioning
confidence: 99%
“…We only focused on the interaction between two social issues. However, it has been found that two related social issues can work jointly to attract public attention from the third issue [38]. In other words, higher-order and more complicated interaction between multiple social issues can exist among social issues to recruit public attention.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the solutions the main visualization adopts a time‐based visual models, using the horizontal axis to represent time and the vertical one to represent volume of documents. Stacked graphs, area charts and stream graphs [BW08] are widely used to visually represent the change in volume of the same object [WLS∗10,LYK∗12] When dealing with topics aggregating over time alluvial diagrams [RB10], are used to provide an idea of flows tearing apart and reconnecting [CLT∗11,SWL∗14,LYW∗16].…”
Section: Related Workmentioning
confidence: 99%
“…Wu et al Wu et al (2014) also focused on the diffusion of opinions and developed a visual analytics system to measure opinion propagation among Twitter users and FluxFlow Zhao et al (2014) focused on the analysis of anomalous information spread. Sun et al Sun et al (2014) modeled the competition process among topics by measuring the influence of topic leaders and designed a time-based visualization, EvoRiver, to explore such interactions.…”
Section: Information Flow Visualizationsmentioning
confidence: 99%